METROLOGY IS THE, OFTEN INVISIBLE, INFRA-TECHNOLOGY SUPPORTING THE QUALITY INFRASTRUCTURE - B.G‘aibnazarov; M.Qurbanbayev (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Metrology remains a uniquely important endeavour. A sign of its success and robustness as an infra-technology is that it usually goes unnoticed. This means that it is in danger of being under-valued and under-appreciated. The sure-footing that metrology provides to the quality infrastructure will be especially important as the world grapples with the aftereffects of the COVID-19 pandemic, rebuilding global economies and also re-focusing on addressing global grand challenges and exploiting emerging technologies. In this context it is important and timely to re-examine the concept of metrology and how it relates to the quality infrastructure that it serves, but differs to measurement in general. The concept of metrology as ‘measuring measurement’ is proposed, emphasising the characteristic meta-thought associated with the discipline that distinguishes it from routine measurement.